THE FORMS OF PRODUCTION OF ALTERNATIVE ENERGY IN ALBANIA - Nikollari, Fejzo (European Scientific Journal, ESJ, 2014)
In this article are given on alternative energy considerations, including these forms of production: • Solar Energy (Photovoltaic) • Wind Energy • Biomass Energy • Biogas • Biodiesel Where are given technological considerations for the application of each case in the Albanian territory.